Factors that motivate blood donor towards blood donation : case study at Sarawak General Hospital blood bank and blood donation drivers / Audrey Annabel Chimbi and Ferra Griffin - Chimbi, Audrey Annabel; Griffin, Ferra (2017)
Blood donation is a way to collect blood for blood transfusion. Due to the fact that there is no substitute to blood products, frequent and steady blood donation is required to maintain blood supply. Thus this study is to study the factors that motivate blood donor towards blood donation. A sample of 98 respondents participated in the study. The study on the other hand, took place at Sarawak General Hospital blood bank and blood donation drives. Firstly, the finding showed that respondents of 28 to 47 years old, male and post graduates were motivated to donate blood. Next, the finding also indicated that the blood donation incentives offered encouraged the blood donor to donate blood. Last but not least, the blood donor had adequate knowledge about blood donation. The finding was able to answer the all research objectives determined by researchers. Consequently, the study was beneficial to the blood bank and other policymakers in order to close the gap between blood supply and blood demand as well as to attain the voluntary blood donation goal.